PERLINDUNGAN ANAK DALAM PANDANGAN ISLAM - Cikka, Hairuddin (Musawa: Journal for Gender Studies, 2022)
The concept in Islam reminds every parent to prepare their children as well as possible, and do not leave them in a weak state, either weak in wealth, weak in education, especially weak in faith, because it will be dangerous for their children. Allah SWT says: "And fear Allah those who, if left behind them weak children, who they worry about (their welfare). Therefore, let them fear Allah and let them speak the truth." (Q.S. an-Nisa: 9). Islamic teachings really protect children because children are a gift as well as a mandate from Allah to parents who must be nurtured and educated as well as possible so that they become human beings with noble character (akhlaqul karimah), physically strong, mentally strong, and strong faith.